2001
DOI: 10.1002/1097-4636(200104)55:1<96::aid-jbm130>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Controlled delivery of taxol from poly(ethylene glycol)-coated poly(lactic acid) microspheres

Abstract: The development of injectable microspheres for sustained drug delivery to the arterial wall is a major challenge. We demonstrated the possibility of entrapping an antiproliferative agent, taxol, in poly(ethylene glycol) (PEG)-coated biodegradable poly(lactic acid) (PLA) microspheres with a mean diameter of 2-6 microm. A solution of taxol and PLA dissolved in an acetone/dichloromethane mixture was poured into an aqueous solution of PEG [or poly(vinyl alcohol) (PVA] with stirring with a high-speed homogenizer fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…But serious side effects are associated with the use of Cremophor EL, including hypersensitivity reaction, nephrotoxicity, neurotoxicity and cardiotoxicity (9,10). Many novel delivery systems of paclitaxel have been investigated to reduce the side effects, such as parenteral emulsion (11), liposomes (12,13), nanoparticles (14)(15)(16)(17)(18)(19), micro-or nanospheres (20)(21)(22)(23)(24)(25), mixedmicelles (26), polymeric micelles (27)(28)(29)(30) and conjugates (31)(32)(33). The drug encapsulation abilities of these systems are affected by many parameters, such as polymer composition, drug feeding amount, fabrication method, etc.…”
Section: Introductionmentioning
confidence: 99%
“…But serious side effects are associated with the use of Cremophor EL, including hypersensitivity reaction, nephrotoxicity, neurotoxicity and cardiotoxicity (9,10). Many novel delivery systems of paclitaxel have been investigated to reduce the side effects, such as parenteral emulsion (11), liposomes (12,13), nanoparticles (14)(15)(16)(17)(18)(19), micro-or nanospheres (20)(21)(22)(23)(24)(25), mixedmicelles (26), polymeric micelles (27)(28)(29)(30) and conjugates (31)(32)(33). The drug encapsulation abilities of these systems are affected by many parameters, such as polymer composition, drug feeding amount, fabrication method, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Microspheres are attracting increasing interest because of their diverse applications in the field of drug [16][17][18][19] and growth factor [20][21][22][23] delivery for tissue engineering. It has been reported that implantation of microspheres containing growth factors resulted in improved cell phenotype and chondrogenesis [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…However, Cremophor EL is biologically and pharmaceutically active, causing anaphylactic hypersensitivity, hyperlipidemia, neurotoxicity, and in vitro cytotoxicity due to the formation of free radicals (9,10). In attempts to overcome the low aqueous solubility of paclitaxel as well as the undesirable toxicity of Cremophor EL, numerous alternate dosage forms have been investigated including gels (11), films (12), emulsions (13)(14)(15), liposomes (16)(17)(18), macromolecule conjugates (19), and particulate delivery systems (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Nanospheres and microspheres containing paclitaxel have been investigated using various polymers such as polylactic-co-glycolic acid (PLGA) (21,(30)(31)(32)(33), poly-lactic acid (24,25), poly-ethylene oxide (25,26,31), poly-propylene oxide (27), and poly(-caprolactone) (20). The proposed advantages of particulate delivery systems for paclitaxel are that they 1) may avoid the use of toxic polyethoxylated castor oil, 2) may evade cellular efflux pumps, 3) can be administered orally or systemically, 4) inhibit tumor growth as well as prevent relapse after surgery, and 5) sustain the release of paclitaxel at therapeutic concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation